Avaliação das variáveis cardiorrespiratórias, metabólicas, marcadores inflamatórios e dos polimorfismos genéticos da APOB e da ECA, em pacientes com doença arterial coronariana e/ou fatores de risco submetidos ao treinamento físico intervalado - Tamburús, Nayara Yamada (2015)
Interval training (IT), combined with pharmacological therapy, has been strongly recommended for the management of coronary artery disease (CAD) and control of cardiovascular risk factors. However, the best protocol to be used it is still unclear. In this regard, the IT protocols based on ventilatory anaerobic threshold (VAT) can be an effective and safe strategy to prescribe the intensity of the exercise training as well as to promote improvement of the aerobic functional capacity, metabolic profile, cardiac autonomic modulation and to reduce inflammatory markers. Moreover, the adaptive responses to IT may differ between individuals. Part of this biological variability may be explained by the genetic polymorphisms involved in the synthesis of structural proteins or on the circulation enzymes. Based on this context, this thesis involved three studies. The first and second studies were conducted to investigate if the IT, based on intensities between 70 and 110% of the workload obtained in the VAT, could be effective to improve functional aerobic capacity and metabolic profile. Moreover, it was investigated if there was a relationship between the improvement in cardiac autonomic modulation with the reduction of the Creactive protein (CRP) in patients with CAD and/or cardiovascular risk factors. The results of the first study showed that the IT program increased aerobic functional capacity and reduced body mass and body mass index. The second study found that after the IT program, there was an increase of the parasympathetic autonomic modulation that was associated with a reduction in CRP levels. Given these findings, the third study was designed to investigate the improvement of the functional aerobic capacity and changes in lipid profile induced by IT, in relation to the apolipoprotein B (APOB) and the angiotensinconverting enzyme (ACE) genes polymorphisms. In this study, it was observed that the increase of the functional aerobic capacity was associated with the presence of the ACE I allele, whereas patients with polymorphism -7673G>A, in the APOB gene, presented increase of the low-density lipoprotein (LDL) levels over time. Considering the findings from these studies, the IT protocol promoted improvement of cardiac autonomic modulation, increase of aerobic functional capacity, reduction of inflammation e improvement of metabolic profile. These benefits on the cardiovascular and metabolic systems contribute to control of cardiovascular risk factors and primary and secondary prevention of CAD. Moreover, this IT protocol provides new possibilities on cardiac rehabilitation field, with respect to exercise training prescription at the VAT level.